OPEC past and present - Kubbah, Abdul Amir Q.; Organisation of the Petroleum Export Countries (OPEC) (Vienna : Petro-Economic Research Centre, 1974)
This book examines the Organisation of the Petroleum Export Countries (OPEC) its nature, achievements, and prospects. It is dedicated to the presentation of an authentic account of the Organization's history over the first fourteen years of its existence. Chapter I discuss the origin of OPEC which is directly attributed to the "successive unilateral cuts in oil prices by the major oil companies in 1959 and 1960. Chapter II is a description of the Organization's status, membership and objective. Chapter III provides a detailed account of the structure of OPEC, which comprises the Conference, Board of Governors and the Secretariat. Chapter IV outlines early successes, the accomplishments of the Organization in the first decade of its life. Chapter V examines the emergence of a sellers' market early in the 1970s. Other chapters include: VI monetary disturbance; VII participation; VIII current and future role of OPEC; IX OPECs thinking-statement of member countries spokesmen; X OPECs thinking-statements by Secretaries General and other OPEC$1 (Bs spokesmen; and XI a survey of member countries oil industry.s
Includes bibliographical references: p. 183-185.
lje 21/01/2019
Loans
Keywords: Oil and gas